Aid and Gendered Subjectivity in Rural Guatemala. Issue 12 (2nd December 2017) - Moore, J.; Webb, M. F.; Chary, A.; Díaz, A. Kraemer; Rohloff, Peter
Abstract: Development discourse has focused on gendered dimensions of poverty, demonstrating how parastatal poverty alleviation programmes target women as aid recipients while devaluing their productive and reproductive work. However, seldom analysed is how privatisation of social services and proliferation of non-governmental organisations (NGOs) have impacted women. We explore this in a Guatemalan community where we find that although NGOs discursively commit to 'alternative' development approaches, on the ground they reproduce elements of a neoliberal subjectivity akin to parastatal programmes. NGOs additionally configure aid disbursement as gift giving, requiring beneficiaries to assume affective postures of gratitude, and facilitating intrusion into women's lives.